2017
DOI: 10.1186/s12917-017-1321-z
|View full text |Cite
|
Sign up to set email alerts
|

Bovine tuberculosis visible lesions in cattle culled during herd breakdowns: the effects of individual characteristics, trade movement and co-infection

Abstract: BackgroundBovine tuberculosis (bTB), caused by Mycobacterium bovis, remains a significant problem for livestock industries in many countries worldwide including Northern Ireland, where a test and slaughter regime has utilised the Single Intradermal Comparative Cervical Tuberculin (SICCT) test since 1959.We investigated the variation in post-mortem confirmation based on bTB visible lesion (VL) presence during herd breakdowns using two model suites. We investigated animal-level characteristics, while controlling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 79 publications
2
46
0
Order By: Relevance
“…Other research using a smaller dataset suggested that liver fluke status did not have an impact bTB lesion presence (Byrne et al. ) but was associated with smaller lesions (Byrne, Graham, Brown, et al. ).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Other research using a smaller dataset suggested that liver fluke status did not have an impact bTB lesion presence (Byrne et al. ) but was associated with smaller lesions (Byrne, Graham, Brown, et al. ).…”
Section: Discussionmentioning
confidence: 88%
“…This abattoir handles the majority of animals (~99%; Byrne et al. ) that were skin test (SICTT) test positive, and therefore the animals processed represent a wide geographic sample across NI (see Milne et al. for distributions).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ireland, IRs that were negative at re-test were followed over a four-year period, and 9.3% of these animals were subsequently diagnosed with TB compared to 2.6% of control animals [13]. In Northern Ireland, in a high-risk cohort, animals with an inconclusive penultimate skin test result had an elevated adjusted odds ratio (OR) of 2.84-3.89 (p < 0.001) relative to non-reactors for the presence of bTB lesions at slaughter [14]. In England and Wales, IR-only herds were 2.7 times more likely to have a subsequent incident compared with negative-testing herds, although this difference reduced over time [15].…”
Section: Introductionmentioning
confidence: 99%